Implementasi E-Budgeting in the Era of the COVID-19 Pandemic at the Regional Secretariat of Sidoarjo Regency: E-Budgeting di Era Pandemi COVID-19 pada Sekretariat Daerah Kabupaten Sidoarjo - Oni Permatasari; Sarwenda Biduri (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to find out how to implement E-budgeting at the Sidoarjo Regency Regional Secretariat in the COVID-19 Pandemic Era. This is a qualitative descriptive study that uses an interpretive study to achieve maximum results.This study uses a system that has several programs to support the success of e-budgeting including: RDS (Regional Development System) and SIKSDA (Regional Financial Information System).The results of this study indicate that the implementation of E-budgeting at the Regional Secretariat of Sidoarjo Regency has been carried out well. The COVID-19 pandemic that occurred had an impact on all aspects, including in the field of Government, so that it could affect the budgeting process. One of them is by seeking budget effectiveness. The Sidoarjo Regency Regional Secretariat as one of the Government aspects in the Sidoarjo Regency Regional Government also received an indicative ceiling from the Regional Planning Board to refocus the budget. By already using e-budegting at the Sidoarjo Regency Regional Secretariat, this is very helpful in accelerating the implementation of budget refocusing. So that the planning process and budget changes can be carried out effectively and efficiently.